Invisibility of Racism in the Global Neoliberal Era: Implications for Researching Racism in Healthcare - Ahlberg, Beth Maina; Hamed, Sarah; Thapar-Björkert, Suruchi; Bradby, Hannah (Frontiers in Sociology, 2019)
This paper describes the difficulties of researching racism in healthcare contexts as part of the wider issue of neoliberal reform in welfare states in the age of global migration. In trying to understand the contradiction of a phenomenon that is strongly felt by individuals and yet widely denied by both institutions and individuals, we consider the current political and socio-economic context of healthcare provision. Despite decades of legislation against racism, its presence persists in healthcare settings, but data on these experiences is rarely gathered in Europe. National systems of healthcare provision have been subject to neoliberal reforms, where among others, cheaper forms of labour are sought to reduce the cost of producing healthcare, while the availability of services is rationed to contain demand. The restriction both on access to, and expansion of welfare, including healthcare, is unpopular among national populations. However, the explanations for restricted access to health care are assumed to be located outside the national context with immigrants being blamed. Even as migrants are used as a source of cheap labour in healthcare and other sectors, the arrival of immigrants has been held responsible for restricted access to healthcare and welfare in general. One implication of (im)migration being blamed for healthcare restrictions, while racism is held to be a problem of the past, is the silencing of experiences of racism, which has dire consequences for ethnic minority populations. The implications of racism as a form of inequality within healthcare and the circumstances of researching racism in healthcare and its implication for the sociology of health in Sweden is described.